An update on drug–drug interactions associated with proton pump inhibitors. (4th May 2022) - Ben Ghezala, Inès; Luu, Maxime; Bardou, Marc
ABSTRACT: Introduction: Proton pump inhibitors (PPIs) block the gastric H/K-ATPase, therefore inhibiting acid gastric secretion, leading to an increased pH (>4). They account for an extremely high number of prescriptions worldwide. Numerous drug–drug interactions have been described with PPIs, but all the described interactions do not have clinical significance. Areas covered: This review will discuss the latest updates on drug–drug interactions with PPIs, focusing on the last 10-year publications in the following areas: anti-infective agents, anticancer drugs, antiplatelet agents and anticoagulants, and antidiabetics. Expert opinion: Although pharmacokinetic interactions of PPIs have been described with many drugs, their clinical relevance remains controversial. However, given the extremely high number of people being treated with PPIs, clinicians should remain vigilant for interactions that may be clinically significant and require dose adjustment or therapeutic monitoring. Interestingly, not all PPIs have the same pharmacokinetic and pharmacodynamic profile, with some having a strong potential to inhibit CYP2C19, such as omeprazole, esomeprazole, and lansoprazole, while others, pantoprazole, rabeprazole, and dexlansoprazole, are weak CYP2C19 inhibitors. These may be preferred depending on co-prescribed treatments. In addition, new formulations have been developed to prevent some of the gastric pH-dependent drug interactions and should be evaluated in further large-scale prospective comparative studies.